2021
DOI: 10.1111/gwao.12761
|View full text |Cite
|
Sign up to set email alerts
|

If I knew then what I know now

Abstract: In this essay, I present an autoethnographic account of my gender affirmation surgery and subsequent recovery. Surgery is considered as the benchmark for people like me but remains little discussed. In the organizational literature the focus is on those who may transition and those who have transitioned, not on the surgery itself. It is glossed over in popular accounts to leave the impression that one goes to sleep one day and wakes fully formed the next. These accounts pay little heed to the somatic, embodied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In 16 studies, the lack of expedient gender-affirming health care was the second most reported barrier to treatment reported by nonbinary adults. Many nonbinary participants reported that they had to wait several months to begin gender-affirming hormones (Davis et al, 2021; Vermeir et al, 2018) or surgery (Chung, 2021; O’Shea, 2022). One nonbinary participant even reported that they waited at least a year to make initial contact with their gender clinic (Burchell et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In 16 studies, the lack of expedient gender-affirming health care was the second most reported barrier to treatment reported by nonbinary adults. Many nonbinary participants reported that they had to wait several months to begin gender-affirming hormones (Davis et al, 2021; Vermeir et al, 2018) or surgery (Chung, 2021; O’Shea, 2022). One nonbinary participant even reported that they waited at least a year to make initial contact with their gender clinic (Burchell et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Scholars exploring “feminine writing” commonly criticize that the management discourse in books and theory tends to appear gender‐neutral, objective, and disembodied—but in reality is not (Phillips et al., 2014; Pullen, 2018). It erects a masculine norm that pushes to the margins women as “the abject” (Höpfl, 2000) as well as—increasingly emphasized in recent research—non‐binary people (O’Shea, 2022a), people of color (Gündemir et al., 2014), women of color (Rabelo et al., 2021), and also individuals affected by intersectional discriminations, and also white cisgender men who reject the status quo and see themselves as allies.…”
Section: Discussionmentioning
confidence: 99%
“…Arts‐based methods, which are able to counter masculine stereotypes of rationality, rigorous method, and explicit knowledge production, have already been considered as possible extensions of “writing differently”, for example, with regard to “feminine writing” (Biehl‐Missal, 2015). Included here are poetic and auto‐ethnographic forms of writing and creative research notes (e.g., Amrouche et al., 2018; Boncori & Smith, 2019; Helin, 2020; O’Shea, 2019, 2022a; Pullen & Rhodes, 2008; Pullen, 2018; Sayers & Jones, 2015; Vachhani & Pullen, 2019), visual narratives and imagery, fabrics and materials (Rippin, 2015), and various kinds of performances (Biehl‐Missal, 2015). For example, Carreri's (2022) artistic installation and video on gender inequalities disseminate research findings differently, enabling empathetic sharing and conveying the affective dimension of individuals' real life experiences.…”
Section: Writing Differently and Artistic Researchmentioning
confidence: 99%